Wound Care Education from a Podiatry Perspective - Wijlens, Anke (Springer, 2025)
Podiatrists have a key role in the diagnosis and treatment of wounds in the lower limb or feet, particularly among patients with diabetes, rheumatic conditions and complications due to cancer treatment. Wound care is essential to patient-centred care, especially in a multidisciplinary environment. Podiatry education provides a variety of competencies that are needed in wound care. A comprehensive understanding of wound aetiology, the healing process and care options is needed to identify, care for and monitor (follow-up) wounds. The podiatry competencies in biomechanics and offloading significantly contribute to the healing process. Podiatrists are educated to relieve and distribute pressure in the wound area by making insoles, orthoses and footwear modifications. In podiatry education, a multidisciplinary approach to wound care is highlighted, realised through collaborative learning and on-site learning with different healthcare professionals during clinical placements. Sustainability in wound care is emphasised in podiatry education to decrease the waste related to wound care and the overall care process. This chapter defines podiatry and describes the main wound care areas in podiatry. Then, wound care competence areas are described with some curriculum-related examples. Finally, methods of teaching wound care in podiatry are provided and discussed in light of the multidisciplinary approach and green podiatry. Future research points are highlighted along with these topics.
Wound Care Education in Nursing : A European Perspective